DEVELOPMENT OF STUDENTS ’INTEREST IN SUBJECTS IN HIGHER EDUCATION INSTITUTIONS: DEVELOPMENT OF STUDENTS ’INTEREST IN SUBJECTS IN HIGHER EDUCATION INSTITUTIONS - to’ychiyev, sobir (Физическое воспитание, спорт и здоровье, 2022)
The article reveals the importance of developing students of higher educational institutions of interest in subjects, the organization of their classes, the interaction of teachers and students, various technologies, methods, forms and means.